Tingkat Kebugaran Jasmani Siswa Ekstrakurikuler Olahraga di SMA Negeri 1 Surade - Herlan Herlan; Rhama Nurwansyah; Rekha Ratri Julianti (Jurnal Literasi Olahraga, 2021)
The purpose of this study was to determine the results of the physical fitness level of extracurricular students at SMAN 1 Surade, whether they were in the good or poor category. The subjects in this study were all members of the sports extracurricular activities at SMAN 1 Surade with 23 students as respondents. The data collection technique used in this research is descriptive quantitative research. The method used was a survey, while the data collection technique used tests, the results of the study showed that the level of physical fitness of sports extracurricular students at SMAN 1 Surade stated that they were in the "very good" category with a percentage of 0%, in the "good" category with a percentage of 0% , in the "medium" category with a percentage of 86.96%, in the "poor" category with a percentage of 13.04%, and in the "very poor" category with a percentage of 0%. Some suggestions related to this research include: 1) Schools should support all existing extracurricular activities, especially sports extracurricular activities so that they can create professional players from schools 2) For teachers or coaches, they should provide a training method that is easy for players to understand. and always motivate players when training and competing